Desain Karakter untuk Animasi 2D "Tarian dalam Hening" di Pixli Studio - Reviana Susanto, Natasha; Trinawindu, Ida Bagus Ketut; Astuti, Ni Ketut Rini (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
"Tarian dalam Hening," (Dance in Silence) which tells the story of a deaf girl and her passion for performing Balinese dance, is one of the 2D animation projects produced by Pixli Studio. This research aims to explore the character design process in the animation. The method used is data analysis with a project-based learning approach. The stages identified in this research start with brainstorming and discussions to understand the vision and characteristics of each character, gathering references and creating mood boards, making several rough sketches, revising based on feedback, and finishing with lineart and coloring. The results show that good character design can enhance visual appeal and story quality in an animation or story, making it more engaging for the audience.